Radioactive Waste Studies in the Frame of the IEA Cooperative Program on the Environmental, Safety, and Economic Aspects of Fusion Power. (17th November 2017) - Zucchetti, M.; Chang, Z.; El-Guebaly, L.; Han, Jung-Hoon; Kolbasov, B.; Khripunov, V.; Riva, M.; Someya, Y.; Testoni, R.; Tobita, K.
Abstract: Some technological problems of radioactive fusion materials management are being addressed in the paper. These problems are being studied in the frame of the International Energy Agency (IEA) collaborative study on fusion radioactive waste. These studies address the management procedures for radioactive materials following the changeout of replaceable components and decommissioning of fusion facilities. Key issues include clearance levels, hands-on and remote recycling procedures, fusion permanent waste hazard assessment, and detritiation of activated materials.